Incidence correction factors for moderate and severe acute child malnutrition from two longitudinal cohorts in Mali and Burkina Faso - Barba, Francisco M.; Huybregts, Lieven; Leroy, Jef L. (Oxford University Press, 2020)
Child acute malnutrition (AM) is an important cause of child mortality. Accurately estimating its burden requires cumulative incidence data from longitudinal studies which are rarely available in low-income settings. In the absence of such data, the AM burden is approximated using prevalence estimates from cross-sectional surveys and the incidence correction factor K⁠, obtained from the few available cohorts that measured AM. We estimated K factors for severe acute malnutrition (SAM) and moderate acute malnutrition (MAM) from AM incidence and prevalence using representative cross-sectional baseline and longitudinal data from two cluster-randomized controlled trials (Innovative Approaches for the Prevention of Childhood Malnutrition—PROMIS) conducted between 2014 and 2017 in Burkina Faso and Mali. We compared K estimates using a complete (weight-for-length z score, mid-upper arm circumference (MUAC), edema) and partial (MUAC, edema) definition of SAM and MAM. K estimates ranged from 9.4 and 5.7 for SAM, and from 4.7 and 5.1 for MAM in Burkina Faso and Mali, respectively. The MUAC and edema-based definition of AM did not lead to different K estimates. Our results suggest that K can be reliably estimated when only MUAC and edema-based data are available. Additional studies, however, are required to confirm this finding in different settings.